Leaf anatomy of medicinally valuable Melastoma malabathricum L. in Peninsular Malaysia - Go, Rusea; Mohd Yunus, Noor Syaheera; Che Amri, Che Nurul Aini; Shahari, Rozilawati (International Islamic University Malaysia, 2024)
Melastoma malabathricum, commonly known as senduduk, is a member of the Melastomataceae family. It is well-known for its therapeutic and medicinal properties, deeply rooted in local traditional knowledge and supported by scientific evidence. Often considered a robust plant and even labeled as a weed, M. malabathricum can be easily spotted along roadsides. However, despite its potential value, recent publications have provided limited information about its leaf anatomy. This study aimed to improve species identification by thoroughly examining the leaf anatomical characteristics of M. malabathricum. Leaf samples were collected from 10 different locations in Peninsular Malaysia and subjected to laboratory procedures involving sectioning and staining. The prepared permanent slides were then observed under a light microscope. A total of 35 leaf anatomical characteristics, including 10 types of trichomes, were successfully identified. Important characteristics such as the petiole, midrib, marginal outline, paracytic stomata, and vascular bundle types were systematically documented. Notable discoveries included the presence of hypodermal layers, collenchyma cells, druses, mucilage cells, and medullary phloem, all of which are distinctive anatomical traits of M. malabathricum. During the leaf anatomical analysis, it became evident that the majority of examined M. malabathricum samples displayed substantial similarities with minor variations in the combination of trichome types on the leaf surface. These variations might be influenced by ecological and geological factors. Nonetheless, it is essential to emphasize that the types of trichomes and other anatomical characteristics remained consistent within each sample. Consequently, these findings offer valuable insights into the systematic classification of M. malabathricum through the documentation of leaf anatomy characters.